Flipped classroom based on Khan Academy as a student’s problem-solving abilities and cognitive learning outcomes booster - Anggi Liztya Qomara; Bea Hana Siswati; Bevo Wahono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
The 21st century learning demanded students to master the 4C competencies: critical thinking and problem-solving, communication, collaboration, and creativity and innovation, with problem-solving skills significantly influencing students' cognitive learning outcomes. This study utilized the Flipped Classroom instructional model, assisted by the Khan Academy application, as a key factor in educational change. This research aimed to determine the effects related to the implementation of the Flipped Classroom instructional model with the assistance of the Khan Academy application on students' problem-solving abilities and cognitive learning outcomes. The research design employed was quasi-experimental with data collection through observation, interviews, tests, and documentation. The results obtained through Independent Sample t-Test in measuring problem-solving abilities indicated that the Sig. value (2-tailed) was 0.028 for the first indicator (understanding the problem); 0.028 for the second indicator (planning the solution); 0.000 for the third indicator (implementing the solution plan); and 0.001 for the last indicator (checking back). This meant that the results were < 0.05 for each indicator. Another result, namely the Analysis of Covariance (ANCOVA) for cognitive learning outcomes was 0.000. This result showed that the Sig. value was < 0.05. Both results indicated that there was an influence of implementing the Flipped Classroom instructional model with the assistance of the Khan Academy application on student’s problem-solving abilities and cognitive learning outcomes of class X students at SMAN 1 Kutorejo regarding the topic of viruses and their roles.